The Phylogenetic analysis of representative mammalian MUC16 supported by comparative SEA domain and tandem repeat variation - Foenna, Yudi Gebri; Yulisma, Ardhana; Calapoğlu, Nilüfer Şahin (Universitas Muhammadiyah Surakarta, 2026)
MUC16 is one of the largest mammalian mucins and exhibits substantial evolutionary variation in both sequence composition and structural modularity. Comparative analysis of SEA domain composition and tandem repeat architecture is therefore essential for understanding the evolutionary diversification of this gene across mammals. This study investigates the phylogenetic relationships of mammalian MUC16 and examines how variation in SEA domains and tandem repeats contributes to lineage-specific structural divergence. MUC16 nucleotide and protein sequences from 20 mammalian species representing Primates and Rodentia were retrieved from public databases. Multiple sequence alignment and phylogenetic reconstruction were conducted using the Neighbor-Joining method with 1,000 bootstrap replicates. SEA domains were annotated using the SMART database, while tandem repeats were identified with Tandem Repeats Finder. Structural features were evaluated using descriptive statistics, hierarchical clustering, and Spearman’s rank correlation analysis. Phylogenetic reconstruction revealed a clear molecular separation between Primates and Rodentia with strong bootstrap support. Primate species generally exhibited conserved sequences and expanded SEA domain and tandem repeat architectures, whereas rodents displayed higher sequence divergence and reduced structural complexity. A moderate positive association between SEA domain number and tandem repeat count (ρ = 0.44) was observed, although this relationship did not reach statistical significance and is therefore interpreted as a biologically suggestive trend rather than evidence of coordinated evolution. Overall, the results indicate that MUC16 evolution follows lineage-dependent patterns shaped by both sequence divergence and domain-level remodeling. This comparative framework provides an evolutionary context for understanding structural diversity in mammalian mucins and offers a foundation for future functional and genomic investigations.